Influence of production factors on feed intake and feed conversion ratio of grow-finishing pigs - Caio Abércio da Silva (Semina: Ciências Agrárias, 2017)
The aim of this study was to identify and quantify, through mathematical models, the production factors of grow-¿nishing (GF) phases that inÀuence the daily feed intake (DFI) and feed conversion ratio (FCR) in pigs. Sixty-¿ve GF farms were evaluated between 2010 and 2013, linked to a cooperative system located in the western Parana State, Brazil, representing 463 batches, with a mean of 642.79 ± 363.29 animals per batch, equalling approximately 300,000 animals. Forty production factors were considered that related to management, sanitation, installations and equipment, nutrition, genetics and environment on the farms. The DFI was inÀuenced by the barn’s position relative to the sun (P = 0.048), initial body weight (P < 0.0001) and ¿nal body weight (P < 0.0001). It was observed that the FCR was inÀuenced by the barn’s position relative to the sun (P = 0.0001), the use of humidi¿ers/misting (P = 0.03), the presence of composters (P = 0.006), trees on the sides of barns (P < 0.045), the initial body weight of the pigs (P<0.0001) and duration of the grow-¿nishing phase (P < 0.0001). The variables selected in the models explained approximately 44 and 20% of the total variance in the DFI and FCR, respectively, demonstrating that this resource is a good tool for interpreting the factors related to the parameters evaluated.